Omnisubjectivity: Something it is Like to be God - Hasker, William (Roczniki Filozoficzne, 2025)
Omnisubjectivity, proposed as a divine attribute by Linda Zagzebski, is the view that “God grasps all the subjectivity that there is.” My article explains omnisubjectivity and endorses the claim that it should be accepted as an attribute of God. However, I criticize Zagzebski’s claims that omnisubjectivity is compatible with (1) divine timelessness and (2) a kenotic view of the incarnation. If omnisubjectivity is affirmed, those two views must be given up.